Analisis Sebaran Pemanfaatan Internet Blog/Weblog untuk Kategori Bisnis dan Ekonomi di Dunia Maya Indonesia - Cooky Tri Adhikara (Bina Nusantara University, 2010)
Internet Weblog / Blog is a medium of communication that are simple, affordable and easy to build. This cause numbers of Blogs in Indonesia grew rapidly. Bloggers, readers and third-party (Internet Provider, Advertiser, mediators) get the benefits of blogs according to their capacity such as mind-sharing, media discourse, promotions, sales, and many other benefits. There are many categories of blogs. Some studies classify them into various categories. This study focus on the business and economic blog category. The aim of this study is to create blog benefiting map of Indonesia’s virtual society, find any Indonesian particular form of blog benefiting, and to seek any suggestion of blog benefit enhance for society.